What Determines Entrepreneurial Outcomes in Emerging Markets? : The Role of Initial Conditions - Ayyagari, Meghana; Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank Group, Washington, DC, 2015)
Is it the institutions or firm characteristics at birth that shape startups and their early growth in developing countries? Using comprehensive data from the Indian Annual Survey of Industries this paper addresses this question by studying the early lifecycle of firms across diverse institutional environments of regions in India. It finds that the size and characteristics of a start-up at entry are persistent over the first eight years of a firm's life. However, given these initial conditions at entry, institutions do not have much explanatory power in determining growth. The comparative growth rates of large and small start-ups are not significantly different across states with different local institutions or industries with differing reliance on external finance or need for fixed capital. But institutions, particularly the availability of credit, do have an impact on the initial entry process. Access to external finance is associated with greater overall entry, and also smaller sized entry. The results do not appear to be driven by endogeneity of access to credit or sample selection. The results show that the channel through which institutions affect the relative outcomes of young firms is through the initial distribution of firm characteristics at entry rather than their effect on the performance of the firms post entry.